An Investigation Into Performance in English and Critical Thinking Between Two English Courses - Mustaffa, Daniel Hasni (2002)
The purpose of this research is to investigate how General English proficiency (GEP) and critical thinking affects the study of English in two different learning situations; one coded MI005 (S) and the other coded WB012. The observation involves first year UPM bumiputra matriculation science students and first year Kolej Teras Timur (KTT) bumiputra matriculation science students. The Sijil Pelajaran Malaysia English is used as the measurement for GEP while critical thinking is measured by the performance of these two groups answering higher order question:; (HOQ) and lower order questions (LOQ. The UPM subjects undergo an ESP (Science) with critical thinking skills course coded MI0015 (S) while the KTT subjects under a general English course coded WB012. Both English courses lasted 14 weeks. The MI005 (S) course is designed by the researcher under the supervision of the English Unit of the UPM Matriculation Centre. Syllabus and tests pertaining to WB012 are designed by the Education Ministry. The subjects who went thorough the programme are bumiputra first semester matriculation science students who will be qualified for local university entry upon finishing their matriculation programme in fulfilment to the requirements of the respective universities. At the end of both programmes, Higher Order Question (HOQ) test and Lower Order Question (LOQ) test are administered. The effects of critical thinking are observed and investigated by looking at the performance of both groups of subjects in these two tests.